Refinements of Generalized Hölder’s Inequalities - Jingfeng Tian; Wen-Li Wang; Donal O’Regan (Journal of Applied Mathematics)
We present some new versions of generalized Hölder’s inequalities. The results are used to improve Minkowski’s inequality and a Beckenbach-type inequality.